Pemanfaatan Biopori sebagai Sumber Resapan untuk Menjaga Ketersediaan Air di Kelurahan Paruga Kota Bima - Mahendra, Mahendra (Florea : Jurnal Biologi dan Pembelajarannya, 2023)
Research on the effect of using biopore as a source of infiltration to maintain the availability of ground water in the district of Rasanae Barat, Bima City. Lack of water is a problem or disaster for every citizen in urban areas. The purpose of this research is how the effect of the biopore. The method used in this study is to use data collection in the form of measuring the height of the volume of water absorption. The parameters tested in this study were to measure the availability of water every day for 5 days. In this study, 4 infiltration wells and 1 control well were made. The volume of increasing the height of the 1st day (First) hole 1 water volume 0.74, hole 2 water volume 0.7, hole 3 water volume 0.72, hole 4 water volume 0.7. day 2 (two) hole 1 water volume 0.76, hole 2 water volume 0.76, hole 3 water volume 0.77, hole 4 water volume 0.76. day 3 (three) hole 1 water volume 0.8, hole 2 water volume 0.81, hole 3 water volume 0.81, hole 4 water volume 0.79. day 4 (four) hole 1 water volume 0.79, hole 2 water volume 0.77, hole 3 water volume 0.8, hole 4 water volume 0.79. With a total volume of 3.09 holes 1, hole 2 volume 3.04, hole 3 volume 3.1, hole 4 volume 3.04. while those in infiltration wells were seen in control wells with initial height data of 0.7 m, second day 0.75 m, third day 0.8 m and final height 0.8 m. From the results of data analysis, it can be concluded that by making 4 biopore holes and 1 control hole, it shows an increase in water volume of 0.8 by using biopore holes as a source of groundwater infiltration